Social aspects of American Peace Corps volunteerism in Botswana 1966-1997 - Monkge, Moatametsi (Faculty of the Humanities, University of the Free State, 2012)
This research aims to investigate and evaluate the work and reasons behind past and contemporary American Peace Corps (APC) volunteerism in Botswana and the social impact this had on Botswana’s developmental roadmap. The study focused on the APC volunteers, being the largest group of volunteers to have served in Botswana and have since stayed the longest. Approximately 2 058 APC volunteers have served in Botswana over a period of 31 years. Available data indicates that the APC volunteers’ advent into Botswana society and their sincere interest and participation in daily community life endeared them to Batswana, leaving behind a legacy of deep friendship and contentment. The volunteers’ free-spirited mentality is credited for influencing local dress styles, music and dance as well as perceptions of black and white relationships in rural Botswana communities. The author asserts that APC volunteerism was able to impact positively on the lives of Batswana, as the volunteers’ work existed within the vortex milieu of already existing forms of volunteerism such as Botswana’s own motshelo, letsema and ipelegeng – schemes that made it easier for the volunteer to mobilize rural communities for development.
Keywords: American Peace Corps; Volunteerism; International; Development; Botswana; Independence; Assistance; Friendship; Culture